OVERLAP SYNDROME OF ALLERGIC CONTACT DERMATITIS AND ATOPIC DERMATITIS: FOCUS ON PATIENTS' QUALITY OF LIFE AND CLINICAL CASES - Liudmyla V. Konovalenko; Iuliia V. Shcherbakova; Viktor I. Litus; Oleksandr I. Litus (Клінічна та профілактична медицина)
Introduction. The combination of atopic dermatitis (AD) with allergic contact dermatitis (ACD) or the occurrence of ACD on the background of AD has been called overlap syndrome. Due to the debilitating symptom complex, which includes itching, discomfort, pain, sleep disturbances and psychological disorders, the overlap syndrome (OS) of ACD and AD has a significant negative impact on the quality of life.